Hollywood math and aftermath : the economic image and the digital recession - Connor, J. D. (Bloomsbury Academic, 2018)
Money is Hollywood's great theme--but money laundered into something else, something more. Money can be given a particular occasion and career, as box office receipts, casino winnings, tax credits, stock prices, lotteries, inheritances. Or money can become number, and numbers can be anything: pixels, batting averages, votes, likes. Through explorations of all these and more, J.D. Connor's Hollywood Math and Aftermath provides a stimulating and original take on "the equation of pictures," the relationship between Hollywood and economics since the 1970s. Touched off by an engagement with the work of Gilles Deleuze, Connor demonstrates the centrality of the economic image to Hollywood narrative. More than just a thematic study, this is a conceptual history of the industry that stretches from the dawn of the neoclassical era through the Great Recession and beyond. Along the way, Connor explores new concepts for cinema studies: precession and recession, pervasion and staking, ostension and deritualization. Enlivened by a wealth of case studies--from The Big Short and The Wolf of Wall Street to Equity and Blackhat, from Moneyball to 12 Years a Slave, Titanic to Lost, The Exorcist to WALLE, Déjà Vu to Upstream Color, Contagion to The Untouchables, Ferris Bueller to Pacific Rim, The Avengers to The Village--Hollywood Math and Aftermath is a bravura portrait of the industry coming to terms with its own numerical underpinnings